Genome editing in the fall armyworm, Spodoptera frugiperda: Multiple sgRNA/Cas9 method for identification of knockouts in one generation. (July 2020) - Zhu, Guan-Heng; Chereddy, Shankar C.R.R.; Howell, Jeffrey L.; Palli, Subba Reddy
Abstract: The CRISPR/Cas9 system is an efficient genome editing method that can be used in functional genomics research. The fall armyworm, Spodoptera frugiperda, is a serious agricultural pest that has spread over most of the world. However, very little information is available on functional genomics for this insect. We performed CRISPR/Cas9-mediated site-specific mutagenesis of three target genes: two marker genes [ Biogenesis of lysosome-related organelles complex 1 subunit 2 ( BLOS2 ) and tryptophan 2, 3-dioxygenase ( TO )], and a developmental gene, E93 (a key ecdysone-induced transcription factor that promotes adult development). The knockouts (KO) of BLOS2, TO and E93 induced translucent mosaic integument, olive eye color, and larval-pupal intermediate phenotypes, respectively. Sequencing RNA isolated from wild-type and E93 KO insects showed that E93 promotes adult development by influencing the expression of the genes coding for transcription factor, Krüppel homolog 1, the pupal specifier, Broad-Complex, serine proteases, and heat shock proteins. Often, gene-edited insects display mosaicism in which only a fraction of the cells are edited as intended, and establishing a homozygous line is both costly and time-consuming. To overcome these limitations, a method to completely KO the target gene in S. frugiperda by injecting the Cas9 protein and multiple sgRNAs targeting one exon of the E93 gene into embryos was developed. Ten percent of the G0 larvae exhibited larval-pupal intermediates. The mutations were confirmed by T7E1 assay, and the mutation frequency was determined as >80%. Complete KO of the E93 gene was achieved in one generation using the multiple sgRNA method, demonstrating a powerful approach to improve genome editing in lepidopteran and other non-model insects. Graphical abstract: Image 1 Highlights: Knockout of Biogenesis of lysosome-related organelles complex 1 subunit 2 induced mosaic translucent integument phenotype. Knockout of tryptophan 2, 3-dioxygenase induced olive eye color phenotype. Knockout of E93 induced larval-pupal intermediate phenotype. Multiple sgRNA method was used to knockout the E93 gene in one generation.